2018
DOI: 10.20945/2359-3997000000011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk in rural workers and its relation with body mass index

Abstract: Objective Evaluate the propensity of cardiovascular risk in rural workers and, through the Framingham Risk Score (FRS), relate this risk with the classification of Body Mass Index (BMI). Subjects and methods This study is characterized as descriptive and exploratory, with the participation of 138 subjects, ranging between 25-73 years old. Clinical and laboratory analysis of the risk factors contained in the FRS were performed, in addition to the determination of BMI, blood pressure, smoking and physical inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…In the studied population, the levels of dyslipidemia are comparable to those found in rural and urban populations, even with a low percentage of HDL-c changes, due to the high physical activity involved in this type of work practice. Studies in rural communities identified substantial differences in the percentage of hypercholesterolemia, which was 15.9% in Minas Gerais 31 and 58% in Rio Grande do Sul 9 . Data from the ELSA-Brazil cohort 37 found a prevalence of hypercholesterolemia and hypertriglyceridemia of 61.5% and 31.2%, respectively, with a difference between genders only for hypertriglyceridemia, which was almost twice as frequent in men (40.9% versus 23.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studied population, the levels of dyslipidemia are comparable to those found in rural and urban populations, even with a low percentage of HDL-c changes, due to the high physical activity involved in this type of work practice. Studies in rural communities identified substantial differences in the percentage of hypercholesterolemia, which was 15.9% in Minas Gerais 31 and 58% in Rio Grande do Sul 9 . Data from the ELSA-Brazil cohort 37 found a prevalence of hypercholesterolemia and hypertriglyceridemia of 61.5% and 31.2%, respectively, with a difference between genders only for hypertriglyceridemia, which was almost twice as frequent in men (40.9% versus 23.0%).…”
Section: Discussionmentioning
confidence: 99%
“…In the field, modernization processes and the consequent changes in lifestyle and diet have also exposed rural workers to the increased risk of cardiovascular diseases due to elevated levels of lipids, glucose, overweight and accumulated abdominal fat in these workers [6][7][8] . Evidence suggests that the prevalence of cardiovascular diseases and their risk factors is higher in the rural population than in the urban population [9][10][11] and that the consequences of CVDs are one of the main reasons for absenteeism or non-performance of usual activities in this population 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the risk of NCDs throughout adulthood increased with the level of BMI trajectories. Reliable studies have shown that risks of NCDs and mortality increased with BMI based on a single measurement (Bernhard et al, 2018; Berrington de Gonzalez et al, 2010; Narayan et al, 2010; Pereira & Conde, 2023). Other studies have suggested that different patterns of BMI development over time may have cumulative effects on health outcomes; therefore, BMI trajectories may better reflect and provide even stronger evidence for the association between BMI and NCDs (Buscot et al, 2018; Song et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nos últimos dez anos, houve 5.786.923 internações hospitalares por doenças cardíacas no Brasil, segundo o Departamento de Informática do Sistema Único de Saúde, repercutindo em altos custos para o sistema público de saúde. As doenças cardiovasculares (DCVs) são a principal causa de óbito, correspondendo a cerca de um terço do número de mortes no país [1][2][3] .…”
Section: Introductionunclassified